CONTEMPORARY CHANGES IN THE ETHNIC STRUCTURE OF THE POPULATION IN THE AUTONOMOUS PROVINCE OF KOSOVO AND METOHIJA - Milosavljević, Saša; Medojević, Jovo (Bulletin of Natural Sciences Research, 2020)
Twenty years (1999 - 2019) after the end of the conflict in the Autonomous Province of Kosovo and Metohija, it can be stated that nowhere in Europe is there such ethnic segregation of the population as is the case with the AP of Kosovo and Metohija. Following the withdrawal of pumped security forces from the entire territory of Kosovo and Metohija and the entry of the United Nations peacekeeping force into the Serbian Autonomous Province, Kosovo Albanians carried out their persecution from Kosovo through terrorist attacks on Serbs and other non-Albanian populations (Montenegrins, Gorans, Roma, Ashkali) carried out their persecution from Kosovo and Metohija and fundamentally changed the ethnic structure of the Province. An insight into the majority of 223.081 exiles and displaced persons from Kosovo and Metohija indicates an exodus against the Serbs. The number of displaced Roma, Ashkali and Egyptians is estimated at about 100.000. The mass persecution of the Serb and other non-Albanian populations has resulted in tremendous changes in the ethnic structure of the Province, which today, with 93% of the total population, is dominated by Albanians, while other ethnic communities have a participation of 7%.